Towards Adoption of Generative AI in Organizational Settings - Prasad Agrawal, Kalyan (The Journal of computer information systems, 2024)
As an emerging technology, Generative Artificial Intelligence (AI) holds immense potential for application across various levels of business and management. However, current studies have not yet investigated the elements that impact the acceptance and implementation of generative AI tools, such as ChatGPT, within organizational settings. To fully leverage its benefits, organizations must embrace and integrate Generative AI at a comprehensive and profound level, making it a valuable area of study. This study aims to put forth and examine the influencing factors impacting the adoption of generative AI technology by utilizing the Technology-Organization-Environment framework in conjunction with the institutional theory and the diffusion of innovation theory. Data from 108 organizations in India is collected and analyzed, leading to valuable insights and implications that contribute to a deeper understanding of the key determinants of generative AI adoption. The study digs out valuable knowledge for organizations looking to embrace this technology.